Between the Tangible & Intangible Smart Reading of Heritage Buildings - Radwan, Gehan A. N.; Abd El Maksud, Sanaa Ibrahem (Advanced Technologies for Sustainable Systems, 2016)
Information era have brought out several technologies that have added a lot into heritage buildings, starting from documentation technologies, virtual presentation technologies, in addition to various dissemination techniques and technologies that connect the public with heritage buildings and spaces. Never the less, HBIM technologies have provided more depth in dealing with heritage buildings in the scope of efficiency, retrofitting in addition to management. All the previous smart technologies have dealt with tangible aspect of heritage providing a physical reading for buildings and spaces. This paper deals with the results of the use of technology in recording and documenting archaeological heritage buildings and the extent of its success in its goals, including the reading of history through the building to check the logic of the argument of Ebn Rushed in his book ‘The Incoherence of the Incoherence’, where he argues that: “ If one looks into a made of any manufactures without perceiving the wisdom behind such made and the purpose intended, and if it does not stand originally with such wisdom one might think it is possible that there are so made, which agreed in any form and any quantity agreed and put any agreed-volume and in whatever order.” Such argument will be investigated through the analysis of a case study with a proposed methodology to assess the results of retrofitting heritage buildings with the consideration of intangible historical aspects rather than tangible physical aspects alone.